A Worldwide Travel Guide to Sea Turtles - Nichols, Wallace J.; Nahill, Brad; Gaskill, Melissa (Book collections on Project MUSE., 2014)
Sea turtle populations around the world are endangered, and in recent years tourism has been a critical element in worldwide efforts to save them. More travelers seek meaningful experiences that bring them close to nature and wildlife, and opportunities to interact with and help sea turtles now exist at locations around the globe, from remote beaches to urban labs. In A Worldwide Travel Guide to Sea Turtles, a scientist, a conservationist, and a journalist have come together to provide a guide to the places where people can view sea turtles and participate in.